Direct observations of the Antarctic Slope Current transport at 113°E - Pena-Molino, Beatriz; McCartney, Michael S.; Rintoul, Stephen R. (Journal of Geophysical Research: Oceans, 2016)
Author Posting. © American Geophysical Union, 2016. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research: Oceans 121 (2016): 7390–7407, doi:10.1002/2015JC011594. The Antarctic Slope Current (ASC), defined here as the region of westward flow along the continental slope off Antarctica, forms the southern limb of the subpolar gyres. It regulates the exchange of water across the shelf break and provides a path for interbasin westward transport. Despite its significance, the ASC remains largely unobserved around most of the Antarctic continent. Here we present direct velocity observations from a 17 month current meter moored array deployed across the continental slope between the 1000 and the 4200 m isobaths, in the southeastern Indian Ocean near 113°E. The observed time-mean flow consists of a surface-intensified jet associated with the Antarctic Slope Front (ASF) and a broader bottom-intensified westward flow that extends out to approximately the 4000 m isobath and is strongest along the upper slope. The time-mean transport of the ASC is −29.2 Sv. Fluctuations in the transport are large, typically exceeding the mean by a factor of 2. They are mainly due to changes in the northward extent of the current over the lower slope. However, seasonal changes in the wind also drive variations in the transport of the ASF and the flow in the upper slope. Both mean and variability are largely barotropic, thus invisible to traditional geostrophic methods M.S.M. and the current meter array were supported by the National Science Foundation grant 0727045 ‘‘Measuring Westward Recirculation in the Subpolar Gyre of the Southeastern Indian Ocean.’’ B.P.M. and S.R.R. were supported by the Cooperative Research Centre program of the Australian Government, through the Antarctic Climate and Ecosystems Cooperative Research Centre. S.R.R. was also supported by the Australian Government Department of the ...